PERSEPSI PEGAWAI TERHADAP PENILAIAN KINERJA PEGAWAI OLEH PIMPINAN BIRO UMUM DI KANTOR GUBERNUR PROVINSI SUMATERA BARAT - Sridiawati (Universitas Negeri Padang, 2014)
This study aims to determine the employee’s perception of the employee performance appraisal by the leadership of the General Bureau in the Office of the Gubernur of West Sumatra Province. Ni is a descriptive study. The population in this study all employees of the Bureau of the General Office of the Gubernur of Sumatra Barat. Populasi many as 151 people and as many as 43 samples. In general, an employee’s perception of the employee performance appraisal by the leadership in the Office of the Gubernur General Bureau of West Sumatra Province with an average score overall was 4,21. From the research it can be said that the employee’s performance appraisal by the leadership of the General Bureau in the Office of the Gubernur of West Sumatra have been implemented properly. Key word:Employee Performance Appraisal